HUBUNGAN ANTARA KOMPETENSI PENYULUH PERTANIAN DENGAN KINERJA KELOMPOK TANI (Studi Kasus di Wilayah UPT-Balai Penyuluhan Pertanian Kecamatan Ngantang, Kabupaten Malang) - Ngongo, Ferdinandus Bili; Muljawan, Rikawanto Eko; Mutiara, Farah (Fakultas Pertanian, 2018)
Agricultural development can be realized with qualified human resources, reliable and capable managerial, entrepreneurship and Organization, so that the perpetrator of agricultural development able to build business from upstream to down stream that is competitive and able to apply the principle of sustainable agriculture development. Objective : To find out the competence of agricultural extension. Farmer group performance, agricultural extension counselor competency with farmer group performance. The research was conducted in the Region of UPT-Counseling Center of Ngantang District of Malang Regency. This research uses quantitative method, which is analyzing and presenting facts systematically so that it is easy to be understood and displayed. The result of the research can be concluded that : Agricultural extension competence based on standard value range 10-50, from 7 counselor, the average value obtained 40. That means extension coach have high competence. The performance of farmer groups is based on the standard range of 10-50, of 56 farmer groups, the average value obtained is 37.13. This means that the group has a high performance. Result of data analysis from both research variables, obtained correlation coefficient value (r-count) of 0.805 and significance value or probability (sign) of 0.029. The value of the correlation coefficient (r-count) is greater than r-table, ie (0.805> 0.339) and the value of probability (sign) of 0.029 < ? 0.05 (5%), so H1 is accepted and H0 is rejected. This means there is a significant relationship between the competence of agricultural extension (variable X) with the performance of farmer groups (variable Y) in the UPT. Pembangunan Pertanian dapat terwujud dengan Sumberdaya manusia yang berkualitas, handal serta berkemampuan manajerial, kewirausahaan dan Organisasi, sehingga pelaku pembangunan pertanian mampu membangun usaha dari hulu sampai hilir yang berdaya saing serta mampu menerapkan prinsip pembangunan pertanian berkelanjutan. Tujuan : Untuk mengetahui.kompetensi penyuluh pertanian. Kinerja kelompok tani, hubungan kompetensi penyuluh pertanian dengan kinerja kelompok tani. Penelitian dilaksanakan di Wilayah UPT-Balai Penyuluhan Kecamatan Ngantang Kabupaten Malang. Penelitian ini menggunakan metode kuantitatif, yaitu menganalisis dan menyajikan fakta secara sistematis sehingga mudah dipahami dan ditampilkan. Hasil penelitian dapat disimpulan bahwa : Kompetensi penyuluh pertanian berdasarkan standart rentang nilai 10-50, dari 7 orang penyuluh, rata-rata nilai yang diperoleh 40. Artinya penyuluh memiliki kompetensi yang tinggi. Kinerja kelompok tani berdasarkan standart rentang nilai 10-50, dari 56 kelompok tani, rata-rata nilai yang diperoleh 37,13. Artinya kelompoktani memiliki kinerja yang tinggi.Hasil analisa data dari kedua variabel penelitian, diperoleh nilai koefisien korelasi (r-hitung) sebesar 0,805 dan nilai signifikansi atau probabilitas (sign) sebesar 0,029. Nilai koefisien korelasi (r-hitung) ini lebih besar dari r-tabel, yaitu (0,805 > 0,339) dan nilai probabilitas (sign) sebesar 0,029 < ? 0,05 (5%), sehingga H1 diterima dan H0 ditolak. Artinya ada hubungan yang signifikan antara kompetensi penyuluh pertanian (variabel X) dengan kinerja kelompok tani (variabel Y) di wilayah UPT.